Model Kearifan Lokal dalam Konteks Pembangunan Pariwisata - Azhar; Agussabti; Indra (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2018)
Local wisdom is one of the cultural values that are still manifest in the order of life of the people in Indonesia. It is a valuable concept so that it can be used as a guide to behavior in a society. This research was conducted with the aim of (1) analyzing the forms of local wisdom contained in the community and their impact on tourism development; (2) finding models or innovations in forms of local wisdom in an effort to realize sustainable development in general and tourism development in particular. This study was conducted at Gampong Aneuk Laot and Gampong Iboih by involving community elements, namely the Village Head, Tuha Peuet, Religious Leaders, cultural figures and tourism actors. Overall, it can be concluded that the value of local wisdom, especially environmental aspects, is a driving factor for proper economic and socio-cultural aspects to be used as a model of local wisdom that can guarantee the sustainability of tourism development.